AB0092 Controlled Expression of Endogenous Interleukin-4 for Gene Therapeutic Approaches towards Rheumatic Disorders. (10th June 2014) - Lang, A.; Neuhaus, J.; Pfeiffenberger, M.; Gaber, T.; Ponomarev, I.; Buttgereit, F.; Barnewitz, D.; Schmidt, M.F.G.
Abstract : Background: Rheumatic diseases such as osteoarthritis (OA) and rheumatoid arthritis (RA) rank among the most common musculoskeletal disorders around the globe accounting for marked loss of life quality, considerable disabilities and financial impact on society. However, an effective causal therapy still remains elusive to provide a long-term remedy. Therefore, daily administration of anti-inflammatory/-rheumatic drugs is inevitable and to some extent related to adverse reactions. At the beginning of the 1990s, gene therapy was noted to be a convenient approach to treat rheumatic disorders locally in the affected joint. In vitro and in vivo studies showed promising results, and during recent years first clinical studies were initiated. Promising approaches link gene therapeutic technics to tissue engineering methods including optimization of cartilage transplants. To overcome critical challenges such as repeated local gene deliveries and undesirable overexpression of transgene(s), several approaches focus on the expression control. Interleukin-4 (IL-4) provides great advantages compared to other candidate genes, by inhibiting the expression of the pro-inflammatory cytokines, especially IL-1β. Objectives: To achieve a safe gene therapy for OA, we aimed at the expression of therapeutic cytokines in a disease responsive manner by using a newly developed "genetic switch", the cyclooxygenase- 2 promoter (pCox-2). To this end, the pCox-2 is cloned upstream of IL-4 and can be inactivated via the absence of inflammatory mediators leading to disease controlled expression. Hence, this approach can also be applied in case of other rheumatic diseases such as in RA. For effective translation to the clinic we use the horse as naturally occurring model since the disease in this species parallels the human form of OA. Methods: Equine chondrocytes were transfected non-virally comparing a range of different reagents for transfection with pIRES2-EGFP (pI2) and pEGFP-N3 (pN3). For further investigations, we used pN3.IL-4 or pN3.pCox-2.IL-4. Transfection efficiency was measured via flow cytometry. Recombinant equine IL-1β or LPS were compared for its potential to simulate inflammatory conditions. Cytokine expressions were investigated by mRNA analysis. Further tests include proliferation tests (TF-1 cells) and ELISA techniques. Results: The transfection efficiency was increased up to 44% by modifying the vector. The stimulation of equine chondrocytes with either IL-1β or LPS resulted in a 20fold higher mRNA expression of IL-1β compared to control cells. A plasmid vector including IL-4 as therapeutic gene under the control of pCox-2 has been proven its functionality. The IL-4 and Cox-2 mRNA expression was increased by stimulating the cells. Furthermore, the IL-1β expression decreased which was probably caused by the presence of IL-4. Conclusions: Our study shows the promising impact of new generation cartilage transplants combined with gene therapy where the therapeutic gene will only be expressed if inflammatory mediators are present close to the defective joint area. Future investigations focus on the viral gene delivery systems and the application into a 3D in vitro OA model. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1633